How to make a night - Ashman, Linda (HarperCollins, 2004)
After a hectic day, it is time to bring on the night so that a child and her family can finally rest. Annotation. Have you had a bad day? Have things been zooming out of control from the moment you set your feet on the floor this morning? Are you ready for the day to be over? No problem! Just follow these instructions on how to make a night: Find a rope. Make a loop. Let it loose in space. Catch the sun. Pull it down. Find a safe, dark place. Peel the blue from the sky. Squirt some dye in a sink. Dunk the blue in the dye 'til it's black like ink. In this fantastic bedtime tale, a hectic day is put to bed, and a peaceful starry night fills the sky so everyone can rest. Linda Ashman and Tricia Tusa have created a magical world in which the sun and the moon cooperate with a resourceful young girl who is ready to put her busy day behind her and settle down to a good night's sleep -- so she can wake up to another exciting day tomorrow!